Health Literacy and Interprofessional Education: Contributions of Speech-Language Pathologists - Meredith L. Baker-Rush (American Journal of Speech-Language Pathology, 2026)
Purpose: Health literacy and health literacy gaps add layers of complexity in health care. Speech-language pathologists (SLPs) offer a unique skill in addressing health literacy disparities within health care teams and with patient care provision. This commentary discusses the systematic impact of health literacy and health literacy gaps, the impact of interprofessional education (IPE) on health literacy, best practices in IPE as it relates to health literacy, and the potential impact of the SLP's role in reference to health literacy within an interprofessional collaborative practice team context. Conclusions: SLPs are uniquely trained in verbal and nonverbal subtleties of health literacy gap identification and as communication architects to build a repair system. Through early IPE and the commitment to lifelong learning, SLPs lead the call to facilitate a bridge when health literacy gaps surface.